2022
DOI: 10.1155/2022/2141524
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Ultrasound-Guided Access for Coronary Interventions through Distal Left Radial Route

Abstract: Aims. Left distal transradial arterial approach (ldTRA) is a new interventional route that spares right radial artery (RRA) for use in haemodialysis and as bypass graft. Vasant Kunj Left dIstal Transradial ArtEry approach (VKLITE) study aimed to assess the feasibility and safety of ldTRA access during coronary angiography (CAG) and percutaneous coronary intervention (PCI). Methods and Results. Between April 2018 and June 2020, 108 patients were enrolled and underwent CAG ± PCI via ultrasound guided ldTRA. Arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…While the use of ultrasound is standard of care for many transvascular interventions, its use in DRA remains at the discretion of the operator and the center's expertise, although there are signals for a higher patient satisfaction and success rate (multiple through-and-through attempts and inadvertent needle injury of underlying periosteum causes severe pain and predisposes to arterial spasm). 27 The same RATATOUILLE study used ultrasound-guided DRA for approximatively 85% of participants which highlights the effectiveness of US use in both DRA and TRA. 24 In relation to hemostasis, DRA showed significantly shorter times.…”
Section: Current Landscape Of Distal Radial Accessmentioning
confidence: 91%
“…While the use of ultrasound is standard of care for many transvascular interventions, its use in DRA remains at the discretion of the operator and the center's expertise, although there are signals for a higher patient satisfaction and success rate (multiple through-and-through attempts and inadvertent needle injury of underlying periosteum causes severe pain and predisposes to arterial spasm). 27 The same RATATOUILLE study used ultrasound-guided DRA for approximatively 85% of participants which highlights the effectiveness of US use in both DRA and TRA. 24 In relation to hemostasis, DRA showed significantly shorter times.…”
Section: Current Landscape Of Distal Radial Accessmentioning
confidence: 91%
“…A total of 3,581 articles were initially retrieved. Based on the titles and abstracts and removing duplicate articles, a total of 22 studies were ultimately enrolled (2,6,12,13,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), with thirteen studies from Asia, five from Europe, two from North America, and two from South America. The sample sizes ranged from 42 to 2,775 cases.…”
Section: Application Of Ultrasound In Distal Radial Artery Interventionsmentioning
confidence: 99%
“…The results of a meta-analysis showed that the size of the outer diameter of the vascular sheath was positively correlated with the incidence of RAO (41), and mismatch between the sheath and vessel diameter increased the incidence of RAO. To reduce the risk of vascular injury, an increasing number of studies have focused on the preoperative assessment of the DRA diameter (2,6,12,13,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Selection of suitable sheaths according to the diameter of the DRA appeared to reduce vascular damage (24).…”
Section: Preoperative Measurement Of Vessel Diametermentioning
confidence: 99%
See 2 more Smart Citations